Collaboration Strategy Faculty of Economic and Bussiness Universitas Negeri Surabaya Indonesia to Become a Faculty With a Global Reputation - Hardini, Han Tantri; Susanti; Rahmawati, Fitriana; Susilowati, Fitriah Dwi; Saputra, Irwan Adimas Ganda; Maula, Farij Ibadil (Economics and Business Journal (ECBIS), 2025)
This research aims to determine the form of cooperation development between the Unesa Faculty of Economics and Business and partners from various institutions both domestically and abroad in order to achieve a Faculty with a global reputation. The research method used is a qualitative method where data collection is carried out by conducting in-depth interviews, observation, documentation and Focus Group discussions. The results of this research show that the development of partnership cooperation between the Faculty of Economics and Business, Universitas Negeri Surabaya, Indonesia with domestic and foreign partners includes education, research and community service. Educational activities in the form of lecturer and student exchanges, seminars, proceedings, guest lectures, visiting lecturers/professors, curriculum benchmarking. Collaboration in the field of research takes the form of joint research, joint publication, joint editor and journal reviewer. Collaboration in the field of community service takes the form of outreach activities, training, mentoring and demonstration activities related to partner needs. So far this collaboration has shown a significant positive impact. The results of the research findings can add theoretical and methodological studies to the repertoire of scientific development regarding the study of the importance of collaboration in an organization, especially for higher education institutions. The contribution of this research adds to the study of the importance of cooperation, not only for the benefit of both parties but also for having an impact on the progress of institutions and society. Contribution for educational institutions, both formal and non-formal, to continue to build partnerships and to socialize the importance of cooperation to increase institutional progress, building more networks to strengthen cooperation. The practical implication of this research is that the Faculty of Economics and Business continues to strive for collaborative networks with the aim of increasing and strengthening collaboration networks in accordance with the vision and mission of the Unesa Faculty of Economics and Business. Priority programs in the context of achieving a global reputation can be used as main topics for collaboration with partners. This implication also adds to the study for educational and non-educational institutions that by collaborating, relationships are created to share knowledge, experience and resources to achieve common goals and contribute to the development of society and the nation.